Determinants of Organizational Citizenship Behavior among University Employees in Shandong, China - Yan cui, Han (Business Management and StrategyMacrothink Institute, 2025)
This study is centered on a comprehensive examination of the factors that influence employee organizational citizenship behavior (OCB). In particular, it delves into the intricate relationships between employee job performance, personal development, and job satisfaction, and how these variables impact the manifestation of organizational citizenship behavior within the workplace. The study employs a quantitative analysis method, allowing for a detailed and data-driven exploration of these relationships. The target population for this study consisted of lecturers from Shandong University. Using purposive sampling, 500 questionnaires were distributed, resulting in 412 valid responses, achieving a response rate of 82.4%. Among the respondents, 183 were male, representing 44.42% of the sample, while 229 were female, accounting for 55.58%. Through rigorous data collection and analysis, this study substantiates the positive influence of job performance, personal development, and job satisfaction on employee OCB. These findings underscore the interconnectedness between various facets of employee engagement and their propensity towards altruistic behaviors within the organizational context. The validation of these relationships provides empirical support for the hypotheses posited in the study, consolidating existing theoretical frameworks and contributing to a deeper understanding of the mechanisms driving employee behavior and organizational effectivenes.